In situ nitrided titanium alloys: Microstructural evolution during solidification and wear. (15th January 2015) - Mohseni, H.; Nandwana, P.; Tsoi, A.; Banerjee, R.; Scharf, T.W.
Abstract: Surface and subsurface structural evolution during sliding wear of two in situ nitrided titanium alloys, β Ti–35Nb–7Zr–5Ta (TNZT) and α/β Ti–6Al–4V (Ti64), was studied by cross-sectional transmission electron microscopy coupled with precession electron diffraction. In situ nitriding during the laser engineered net shaping (LENS™) process resulted in the formation of hard and wear-resistant Ti2 N + TiN phases and nitrogen-enriched α phase in TNZT and Ti64, respectively. Subsurface structural analyses of the worn nitrided TNZT revealed the tendency of α grains, and to greater extent β grains, to undergo severe plastic deformation, forming a heavily grain-refined nanocrystalline α and β tribolayer. Corresponding precession–orientation imaging phase maps were used to determine the orientation and percentage of α and β-Ti in the worn nitrided TNZT. The maps revealed that the nanocrystalline grains of soft/compliant β are much smaller (10–100 nm) than hard/stiff α grains (>100 nm). Wear reduction is due to the combination of the above phases and the increase in the alignment of 0 0 0 2-textured coarser α grains along the sliding direction in absence of texture in the highly refined β grains. Conversely, nitrided Ti64 exhibited slightly increasing wear, despite higher hardness, due to the change in sliding-induced deformation mechanism where shear bands formed and networked leading to brittle fracture and third body abrasive wear particle generation.